THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN CHARACTER BUILDING OF STUDENTS: A SYSTEMATIC ANALYSIS OF EMPIRICAL LITERATURE IN SECONDARY SCHOOLS - Muhammad Nur Effendi; Muhammad Yusuf (Adisam Publisher, 2026)
This study systematically analyses empirical literature on the role of Islamic Religious Education (IRE) in shaping the character of secondary school students in Indonesia through a literature review. The findings of this study confirm the effectiveness of IRE in increasing students' religiosity, discipline and social empathy through teacher role modelling strategies, habitual worship, thematic discussions of the Qur'an, and extracurricular religious activities. However, the implementation of PAI is hampered by low teacher pedagogical quality, monotonous methods, the negative influence of social media, and a lack of family-school synergy. Recommendations include a digital PAI curriculum, affective neuroscience teacher training, and collaboration between the Ministry of Education and Culture and the Ministry of Religious Affairs to optimise character based on akhlakul karimah (good character) in the digital era.